Challenges in diagnosing pediatric pericarditis and the etiology in remote areas during the COVID-19 pandemic: a socio-clinical dilemma: A Socio-Clinical Dilemma - Liwan, Armand Setiady; Yantie, Ni Putu Veny Kartika; Gunawijaya, Eka (Indonesian Pediatric Society, 2024)
Inflammation of the visceral and parietal surfaces of the pericardium is defined as pericarditis. It can evolve to excessive production of pericardial effusion if the speed of fluid accumulation is faster than the absorption. Acute pericarditis is rare in children but it can lead to circulatory collapse and death. It accounts for <0.2% of the emergency visits of children without prior heart diseases in tertiary pediatric emergency settings. The etiology of acute pericarditis varies depending on geography, and the most common etiology in children are bacterial infection, viral pericarditis, inflammatory or connective tissue diseases, malignancies, metabolic diseases, and post-cardiac surgery. Idiopathic pericarditis is presumed to have viral or post-viral etiology. It accounts for 37-68% of admissions in children with pericardial effusions or acute pericarditis.